TRANSLATION TECHNIQUES ANALYSIS: THE ACCURACY OF INDONESIAN SUBTITLES IN THE GENSHIN IMPACT GAME《原神》 - Mughni, Ari Abdul; Delijar, Ressi Maulidina (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2024)
The exchange of information between two languages, from the source language (SL) to the target language (TL), requires a process known as translation. The translated text is referred to as the translation product, and during its creation, translation techniques are needed to produce an accurate meaning in the target language. Translation occurs across various media, one of which is in video games. Accurate translation provides clear and directed instructions to players for completing game missions. Therefore, this research aims to examine how translation techniques from Mandarin to Indonesian affect the meaning of translations in several mission dialogue clips from the game Genshin Impact. Descriptive qualitative research method is used to analyze this research. The translation product, consisting of mission dialogue sentences from Genshin Impact, serves as the data analyzed. The data are examined with reference to Molina and Albir’s translation technique theory. The results indicate that the choice of translation techniques can influence the meaning of the resulting translation product. In fact, in the Indonesian subtitles of Genshin Impact, some translation techniques used were found to be less suitable, leading to inaccurate translation meanings.